2018
DOI: 10.1111/mec.14536
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally altered rainfall regimes and host root traits affect grassland arbuscular mycorrhizal fungal communities

Abstract: Future climate scenarios predict changes in rainfall regimes. These changes are expected to affect plants via effects on the expression of root traits associated with water and nutrient uptake. Associated microorganisms may also respond to these new precipitation regimes, either directly in response to changes in the soil environment or indirectly in response to altered root trait expression. We characterized arbuscular mycorrhizal (AM) fungal communities in an Australian grassland exposed to experimentally al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 61 publications
2
36
1
2
Order By: Relevance
“…MAP has a small but significant influence on structuring phyllosphere fungal communities (Table 1), which is in line with the patterns observed in foliar fungal communities of Metrosideros polymorpha across a Hawaiian landscape 13 , in AMF community assembly associated with four plant species in a grassland ecosystem 108 , and in endophytic fungal community of Panicum hallii across the Edwards Plateau 109 . Precipitation can directly influence the fungal species pool, and can also exert important influence on ecosystem processes including respiration, decomposition and plant productivity, as well as may indirectly affect plant-associated fungal communities via changes in the local host community properties 110 .…”
Section: Discussionsupporting
confidence: 80%
“…MAP has a small but significant influence on structuring phyllosphere fungal communities (Table 1), which is in line with the patterns observed in foliar fungal communities of Metrosideros polymorpha across a Hawaiian landscape 13 , in AMF community assembly associated with four plant species in a grassland ecosystem 108 , and in endophytic fungal community of Panicum hallii across the Edwards Plateau 109 . Precipitation can directly influence the fungal species pool, and can also exert important influence on ecosystem processes including respiration, decomposition and plant productivity, as well as may indirectly affect plant-associated fungal communities via changes in the local host community properties 110 .…”
Section: Discussionsupporting
confidence: 80%
“…The outcome of species interaction is altered by climate change effects [144]. For example, fungal communities have been altered because of changes in soil moisture and temperature [145]. It has been reported that drought stress increases root colonization by arbuscular mycorrhizal fungi [146], representing an important strategy for water stress management [147].…”
Section: Effects Of Drought On Plant-soil Microbe Interactionsmentioning
confidence: 99%
“…Within the existing range, the ecological outcome of plant–soil microbe interactions depends not only on plant genes, microbial genes and microbial species composition but also on the environmental context (Hoeksema & Forde, ; Laine, ; Thompson, ). For example, soil moisture and temperature have been shown to alter fungal communities (Deveautour, Donn, Power, Bennett, & Powell, ; Rasmussen et al, ) and may thereby change feedbacks between plants and fungi, for example, if communities change from one more dominated by beneficial microbes to one more dominated by antagonistic microbes or vice versa. As such, environmental change can disrupt both plant local adaptation and plant maladaptation to the local soil microbial community within the present range.…”
Section: Introductionmentioning
confidence: 99%